2012
DOI: 10.1089/jop.2011.0238
|View full text |Cite
|
Sign up to set email alerts
|

Results of Interferon Alpha-2a Therapy in Patients with Behcet's Disease

Abstract: IFN-α-2a treatment is effective in Behcet uveitis refractory to traditional treatment regimens and provides significant improvement in visual prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Open-label studies [Boyvat et al 2000;O'Duffy et al 1998;Georgiou et al 1998;Azizlerli et al 1996;Alpsoy et al 1994] Eye involvement Uncontrolled prospective study [Kotter et al 2003] Retrospective studies [Onal et al 2011;Sobaci et al 2010;Deuter et al 2010;Bodaghi et al 2007;Tugal-Tutkun et al 2006;Deuter et al 2004;Krause et al 2003;Calguneri et al 2003;Hamuryudan et al 2002;Wechsler et al 2000;Yalcindag and Uzun, 2012] Systematic review [Kotter et al 2004a] Mucocutaneous disease and arthritis Uncontrolled prospective study [Kotter et al 2004b] Systematic review [Kotter et al 2004a] Neuro-Behçet Case reports [Nichols et al 2001;Kuemmerle-Deschner et al 2008;…”
Section: ]mentioning
confidence: 99%
“…Open-label studies [Boyvat et al 2000;O'Duffy et al 1998;Georgiou et al 1998;Azizlerli et al 1996;Alpsoy et al 1994] Eye involvement Uncontrolled prospective study [Kotter et al 2003] Retrospective studies [Onal et al 2011;Sobaci et al 2010;Deuter et al 2010;Bodaghi et al 2007;Tugal-Tutkun et al 2006;Deuter et al 2004;Krause et al 2003;Calguneri et al 2003;Hamuryudan et al 2002;Wechsler et al 2000;Yalcindag and Uzun, 2012] Systematic review [Kotter et al 2004a] Mucocutaneous disease and arthritis Uncontrolled prospective study [Kotter et al 2004b] Systematic review [Kotter et al 2004a] Neuro-Behçet Case reports [Nichols et al 2001;Kuemmerle-Deschner et al 2008;…”
Section: ]mentioning
confidence: 99%
“…30 In other studies, the high efficacy of interferon-a-2a for BD with uveitis has also reported in Turkey and France. [31][32][33][34][35][36][37][38] A high incidence of ADRs is to be noted. Flu-like symptoms, including fever and/ or joint pain, occur in most of cases, but they appear only after first injection.…”
Section: Prednisolone (Predonine õ )mentioning
confidence: 99%
“…Since its first use for the treatment of BD in the 1980s, a number of publications have reported on the beneficial effect of IFN- α , usually human recombinant IFN- α -2a, in recalcitrant forms of BU [170178]. Although dose regimens varied, response rates (partial or complete) ranged between 78% and 98% with good functional outcomes and diminished uveitis attack frequencies.…”
Section: Immunologic Relevance Of Biologic Agents In Behçet's Uveitismentioning
confidence: 99%